Pengaruh Likuiditas Dan Laverage Terhadap Profitabilitas (Studi Kasus Pada Perusahaan Farmasi Yang Terdaftar Di Bursa Efek Indonesia Periode 2019-2022) - Mexano Hans Gery (CV. ITTC INDONESIA, 2024)
This research aims to determine the extent of influence, liquidity and leverage on the profitability of pharmaceutical sector manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2022 period. This research is quantitative research. The population of this research is all pharmaceutical sector manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2022 period. Sample selection was carried out using the purposive sampling method and resulted in a selected sample of 35 samples. The data collection technique used is documentation, with documents in the form of company financial reports for 2019-2022. The data analysis technique uses descriptive analysis, classical assumption testing, and hypothesis testing using multiple linear regression analysis with SPSS 16 tools. The results of the research show that: both variables have a significant effect on Y. and an Adjusted R Square value of 0.363 or 36.3 is obtained. % This means that 36.3% of the profitability variable is influenced by liquidity and the remaining 63.7% of leverage is influenced by other variables outside of this research variable.